UPAYA MENINGKATKAN KETERLIBATAN AYAH DALAM PEMENUHAN NUTRISI PADA BALITA: STUDI KASUS ASUHAN KEPERAWATAN KOMUNITAS - Restu Ayuningtyas; Titih Huriah (Jurnal Keperawatan Muhammadiyah, 2026)
Latar Belakang: Nutrisi yang cukup pada masa balita sangat penting untuk pertumbuhan dan perkembangan yang optimal. Keterlibatan keluarga, khususnya peran ayah, memainkan peran penting dalam memenuhi kebutuhan nutrisi balita. Keterlibatan ayah yang terbatas dapat menghambat nutrisi keluarga yang optimal. Studi ini bertujuan untuk memberikan perawatan kesehatan komunitas kepada kelompok ayah untuk meningkatkan keterlibatan ayah dalam memenuhi kebutuhan nutrisi balita. Methods: This study employed a case study design using a community nursing care approach guided by the Community as Partner model. The intervention was conducted over three weeks following the nursing process phases, including assessment, diagnosis, planning, implementation, and evaluation. A total of 11 fathers with children aged 0–60 months were recruited through purposive sampling based on predetermined inclusion criteria. Paternal involvement in fulfilling toddlers’ nutritional needs was measured before and after the intervention using a structured questionnaire that had undergone expert content validation. The intervention consisted of health education sessions addressing the role of fathers in toddler nutrition. Data were analyzed using the Wilcoxon signed-rank test with SPSS to determine differences in involvement scores before and after the intervention. Results: The findings demonstrated an improvement in fathers’ involvement in fulfilling toddlers’ nutritional needs following the community nursing intervention. Fathers showed greater engagement in supporting mothers, food provision, and decision-making related to toddler nutrition. Conclusion: Community nursing care targeting fathers significantly improved toddlers’ nutritional outcomes. Strengthening family-based nutrition education with active paternal involvement is recommended to support improved nutritional outcomes among toddlers. Keywords: Community nursing care, Family role, Health education, Paternal involvement, Toddler nutrition.